Lipoarabinomannan Decreases Galectin-9 Expression and Tumor Necrosis Factor Pathway in Macrophages Favoring Mycobacterium tuberculosis Intracellular Growth - Chávez-Galán, Leslie; Ramon-Luing, Lucero; Carranza, Claudia; Garcia, Irene; Sada-Ovalle, Isabel (Frontiers in Immunology, 2017)
Lipoarabinomannan (LAM) is a lipid virulent factor secreted by Mycobacterium tuberculosis (Mtb). LAM can be found in the sputum and urine of patients with active tuberculosis. When human monocytes are differentiated into macrophages (MDM) in the presence of LAM, MDM are poorly functional which may limit the immune response to Mtb infection. Our previous studies have shown that TIM3 and Galactin (GAL)-9 interaction induces anti-mycobacterial activity, and the expression levels of TIM3 and GAL-9 are downregulated during Mtb infection. We postulated that LAM affects GAL9/TIM3 pathway, and, in consequence, the ability of the macrophage to control bacterial growth could be affected. In this work we have generated MDM in the presence of LAM and observed that the expression of TIM3 was not affected, in contrast, GAL9 expression was downregulated at the transcriptional and protein levels. We observed that the cell surface and the soluble form of TNF receptor 2 were decreased. We also found that when LAM-exposed MDM were activated with LPS, they produced less TNF, and the transcription factor PAR2, which is involved in host immune responses to infection, was not induced. Our data show that LAM-exposed MDM were deficient in the control of intracellular growth of Mtb. In conclusion, LAM-exposed MDM leads to MDM with impaired intracellular signal activation affecting GAL9, TNF and PAR2 pathways which are important to restrict Mtb growth.